PERAN BUMDES DALAM MENDORONG USAHA GULA SEMUT BERBASIS ENERGI TERBARUKAN: STUDI EKONOMI KUALITATIF DI TALAITAD UTARA - Melky Elia Kristna Paendong; Arief Perdana Kumaat; I Gede Para Atmaja; Adelaida Joroh; Dominikus Andreo Maryadi, (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2025)
This study aims to analyze the role of the Village-Owned Enterprise (BumDes) in promoting the development of palm sugar (gula semut) production based on renewable energy in Talaitad Utara Village, Minahasa Selatan Regency. Using a descriptive qualitative approach and a case study method, data were collected through in-depth interviews with the Head of BumDes Tala-Ut Jaya. The findings show that BumDes plays a strategic role not only as a business operator but also as a facilitator connecting local farmers, distributors, and external stakeholders. The integration of photovoltaic systems in the production process has improved energy efficiency and reduced operational costs, strengthening the product's value proposition as an environmentally friendly commodity. However, the business still faces supply chain challenges, particularly the inconsistency of raw materials due to the tendency of local farmers to divert palm sap to produce traditional liquor (cap tikus) during certain seasons, which they perceive as more profitable. The study concludes that renewable energy-based village businesses require not only technological innovation but also socio-economic strategies to ensure long-term sustainability from upstream to downstream. This model provides a valuable reference for developing sustainable rural economies based on local potential and clean energy.